If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x1=1)+2x=2(x+2)
We move all terms to the left:
2(x1-(1)+2x)=0
We add all the numbers together, and all the variables
2(3x-1)=0
We multiply parentheses
6x-2=0
We move all terms containing x to the left, all other terms to the right
6x=2
x=2/6
x=1/3
| 4x+6=×+12 | | (7y+5)-(4+6y)=9 | | 75=500•.05•t | | 2/3(6c+3=6(c-3) | | 15/8x+1/4=4 | | 17x=18x | | 3t^2+11t+6=0 | | 15x-3=8x+8 | | 5/8y+3/4y=4+2y | | -7=-k-4 | | n*0.99=n*1.29 | | (0,3)m=4 | | (4/3)-3=s+(2/3)-(1/3)s | | 7x+4x+4+9=6x+3+4x | | 2/3(h)-156=(3)13/24 | | -x-110-11x=142 | | 17-16(7/8x+-2)=7(7-2x) | | -5t^2+30t+60=0 | | x(x^2-x)=343 | | 58=50+c-40/4 | | -6+x/3=-10 | | 2p+2-9p-9=-4 | | 3q^2+40q+13=0 | | 200=16(6t-3 | | x^2/x+80=40 | | 1/2t+4=3 | | 3/2*n=2/9 | | (5x-17)=(3x+14) | | 5x+5×=5×+4 | | 9v/15=0 | | 15j=3/11j | | -4x+6=-8x+30 |